2015
DOI: 10.3767/003158515x685382
|View full text |Cite
|
Sign up to set email alerts
|

<I>Phytopythium</I>: molecular phylogeny and systematics

Abstract: The genus Phytopythium (Peronosporales) has been described, but a complete circumscription has not yet been presented. In the present paper we provide molecular-based evidence that members of Pythium clade K as described by Lévesque & de Cock (2004) belong to Phytopythium. Maximum likelihood and Bayesian phylogenetic analysis of the nuclear ribosomal DNA (LSU and SSU) and mitochondrial DNA cytochrome oxidase subunit 1 (COI) as well as statistical analyses of pairwise distances strongly support the status of Ph… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
95
0
4

Year Published

2015
2015
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 126 publications
(106 citation statements)
references
References 23 publications
7
95
0
4
Order By: Relevance
“…According to de Cock et al [20], key characteristics for Phytopythium are the following: predominantly papillate sporangia and internal proliferation in most species as well as often constricted and elongate to cylindrical antheridia. However, there is a large degree of variation in sporangium characteristics.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…According to de Cock et al [20], key characteristics for Phytopythium are the following: predominantly papillate sporangia and internal proliferation in most species as well as often constricted and elongate to cylindrical antheridia. However, there is a large degree of variation in sporangium characteristics.…”
Section: Discussionmentioning
confidence: 99%
“…Based on the concatenated sequences of ITS, cox1, cox2, and LSU, USTCMS 4102 belongs to Clade 1 [20,21] of Phytopythium (Fig. 4, Fig.…”
Section: Phylogenymentioning
confidence: 99%
“…These studies reported occurrence of P. undulatum, P. anandrum Drechsler, P. aphanidermatum (Edson) Fitzp., P. irregulare Buisman, P. middletonii Sparrow, P. rostratum Butler and P. intermedium de Bary in oak stands in Austria, Germany, Turkey and Sweden. Of all Pythium species recorded in these studies, P. anandrum and P. undulatum are the most commonly reported and are known as fine root pathogens which may affect the health of oak trees in Europe [9][10][11][12][13] [14]. However, information about the oak-associated Pythium and Phytopythium species is still very limited.…”
Section: Digital Signaturementioning
confidence: 99%
“…Recently, de Cock et al [9] provided molecular-based evidence that members of Pythium clade K as described by Lévesque and de Cock [5] belong to the Phytopythium genus. While recognizing the genus status of remaining species of Pythium clades (A-J) is still unclear we prefer to use to the definition of Pythium sensu Lévesque and de Cook [5].…”
Section: Digital Signaturementioning
confidence: 99%
“…Bala et al, 44 proposed a new genus Phytopythium Abad for those species with globose to ovoid, often papillate and internally proliferating sporangia. Uzuhashi et al, 45 46 In distribution, the species of Pythium are cosmopolitan, widely distributed throughout the world ranging from tropical to temperate 12 and even arctic 47 and antarctic regions. 48 Economically, they are especially important as pathogens of monocotylodonous plants, causing serious damage to cereal crops and turf grasses, leading primarily to soft rot of fruit, rot of roots and stems, and pre-and post-emergence of seeds and seedlings by infecting mainly juvenile or succulent tissues.…”
Section: Pythiummentioning
confidence: 99%